2017
DOI: 10.1097/iae.0000000000001480
|View full text |Cite
|
Sign up to set email alerts
|

Macular Choroidal Volume Changes After Intravitreal Bevacizumab for Exudative Age-Related Macular Degeneration

Abstract: The macular choroidal volume and the subfoveal choroidal thickness decreased significantly after 3 monthly bevacizumab injections for exudative age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…We hypothesized that the anti-VEGF treatment may influence retinal and choroidal exudation, reducing vascular hyperpermeability and resulting in a significant reduction of CMT and SFCT. Similar findings have been reported in earlier studies [23][24][25][26].…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesized that the anti-VEGF treatment may influence retinal and choroidal exudation, reducing vascular hyperpermeability and resulting in a significant reduction of CMT and SFCT. Similar findings have been reported in earlier studies [23][24][25][26].…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that choroid plays an important role in scleral remodeling via the synthesis of several growth factors including VEGF [35], hepatocyte growth factor [36], and basic fibroblast growth factor [37]. Previous studies revealed that IVB and IVR decrease choroidal thickness and volume significantly in an adult population with diabetic macular edema and age-related macular degeneration [38][39][40]. Since diabetic macular edema and ROP are results of retinal vascular disturbances, we can assume that IVB and IVR might cause reduction in choroidal thickness and volume in infants with ROP, which in turn might affect the choroidal mechanisms of emmetropization.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, a decrease in CT was noted in the eyes that underwent anti-VEGF therapy, regardless of the type of anti-VEGF agents used. 9–12 This trend was also noted in eyes with Type 3 MNV, 9,11,13,14 which generally develops in eyes with a very thin choroid. 15,16 It is postulated that the thin choroid in eyes with Type 3 MNV may induce hypoxic conditions in the retina and thus contribute to the development of intraretinal MNV.…”
mentioning
confidence: 70%
“…Although a significant decrease in CT after anti-VEGF therapy has been reported, [9][10][11][12] there has been controversy as to whether this decrease is actually because of the effect of anti-VEGF. In some studies, a decrease in CT was not noted after anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%